Mujeres en prisión por delitos de drogas : un espejo de las fisuras del desarrollo (2017)
"The female prison population has increased in Colombia year after year. This trend is evident in all the countries of the region and in several continents. The main reason why women are arrested is because they commit drug offenses. This research argues that the growing involvement of women in the drug industry is result of the neoliberal development model and a militarized gender order. Prison and the treatment received by women inside of it in drug detention does not speak about the transgression they incurred, it speaks about how the State reacts to the incapability to respond to a development project based on economic growth that excludes and deepens gender inequality. Women in prison dramatically reflect fissures of that model." -- Tomado del Formato de Documento de Grado.